Non-Coding RNA Regulatory Network in Ischemic Stroke - Cai, Zongyan; Li, Shuo; Yu, Tianci; Deng, Jiahui; Li, Xinran; Jin, Jiaxin (Frontiers in Neurology, 2022)
Stroke is a worldwide public health problem that has caused a substantial economic burden to families and society. Despite recent major advances, there is still a need for more timely, effective diagnosis and treatment methods for acute ischemic stroke. Non-coding RNAs (ncRNAs), which widely exist in the human body, do not encode proteins. Instead, these mediate various cellular processes as functional regulatory molecules from the RNA level. Each ncRNA node in organisms is not isolated but constitutes a complex regulatory network, regulating multiple molecular targets and triggering specific physiological or pathological reactions, leading to different outcomes. Abundant studies have proclaimed the impact of ncRNAs in ischemic stroke, which may enlighten new inspirations for diagnosing and treating ischemic stroke. This paper outlines the current understanding of the ncRNA regulatory network and reviews the recent evidence for the contribution of ncRNAs in the experimental ischemic stroke model.